How inter-city high-speed rail influences tourism arrivals: evidence from social media check-in data. Issue 9 (28th May 2019) - Liu, Yang; Shi, Jing
Abstract : This paper attempts to investigate the impacts of inter-city high-speed rail (HSR) on tourism arrivals by employing a novel data of check-ins generated from social media. This type of check-in data collected in a case study (Hangzhou, China) reveals its high correlation with tourism activities and is feasible to act as a proxy of real tourism arrivals. A nonlinear regression model is developed to discover the temporal redistribution of tourism arrivals caused by HSR on weekends and holidays. Results show that Nanjing–Hangzhou HSR can significantly raise the number of visitors from Nanjing with a growth of 29.44% on Saturdays and 41.72% on Sundays. Further analysis on hourly distribution of these check-ins on weekends detects early arrival on Friday nights and longer stay on Sunday afternoons after HSR operates. Moreover, negative effect of seasonal climate change on tourism is also alleviated by HSR. This paper verifies the effectiveness of social media check-in data in tourism research and proposes practicable methodologies to quantitatively analyse this type of data.